The Influence of Halal Literacy, Religiosity, and Fear of Missing Out on the Purchase Decision of Korean Instant Noodles of the Samyang Brand - Arfannisa Febrilianty; Restu Frida Utami; Wida Purwidianti; Arini Hidayah (Transpublika Publisher, 2025)
Indonesia’s instant noodle industry is expanding rapidly, with Samyang gaining popularity among young consumers for its unique flavors and strong online presence. While halal literacy, religiosity, and Fear of Missing Out (FoMO) increasingly shape food choices, few studies have examined their combined impact on purchasing decisions for imported brands like Samyang. This study aims to examine the influence of halal literacy, religiosity, and Fear of Missing Out (FoMO) on purchasing decisions for Samyang brand instant noodles. A quantitative approach was used with a purposive sampling method. The respondents in this study were active university students in the Purwokerto area, Muslim, and had purchased and consumed Samyang instant noodles. To obtain accurate results, the researcher used a sample of 271 respondents and conducted the analysis using SPSS software. The findings indicated that all three variables had a positive and significant influence on purchasing decisions.